Brain Endothelium: The “Innate Immunity Response Hypothesis” in Cerebral Malaria Pathogenesis - Pais, Teresa F.; Penha-Gonçalves, Carlos (Frontiers in Immunology, 2019)
Cerebral malaria (CM) is a life-threatening neurological syndrome caused by Plasmodium falciparum infection afflicting mainly children in Africa. Current pathogenesis models implicate parasite and host-derived factors in impairing brain vascular endothelium (BVE) integrity. Sequestration of Plasmodium-infected red blood cells (iRBCs) in brain microvessels is a hallmark of CM pathology. However, the precise mechanisms driving loss of blood-brain barrier (BBB) function with consequent brain injury are still unsettled and it is plausible that distinct pathophysiology trajectories are involved. Studies in humans and in the mouse model of CM indicate that inflammatory reactions intertwined with microcirculatory and coagulation disturbances induce alterations in vascular permeability and impair BBB integrity. Yet, the role of BVE as initiator of immune responses against parasite molecules and iRBCs is largely unexplored. Brain endothelial cells express pattern recognition receptors (PRR) and are privileged sensors of blood-borne infections. Here, we focus on the hypothesis that innate responses initiated by BVE and subsequent interactions with immune cells are critical to trigger local effector immune functions and induce BBB damage. Uncovering mechanisms of BVE involvement in sensing Plasmodium infection, recruiting of immune cells and directing immune effector functions could reveal pharmacological targets to promote BBB protection with potential applications in CM clinical management.